A Cross-Cultural Investigation of Basic Psychological Need Satisfaction at Work in an Indigenous and Non-Indigenous Australian Sample Across Occupation Types. (February 2022) - Magson, Natasha R.; Craven, Rhonda G.; Ryan, Richard M.; Dillon, Anthony; Mooney, Janet; Blacklock, Fabri; Yeung, Alexander S.; Kadir, Munirah S.; Franklin, Alicia
Self-determination theory (SDT) posits universality without cross-cultural uniformity of the three basic psychological needs (autonomy, competence, and relatedness) which have been associated with desirable job outcomes. Yet these promising directions in theory and research have not been extended to Indigenous samples and different occupational types. This is unfortunate as Indigenous peoples globally remain the most disadvantaged on all socio-economic indicators, including employment. This study adopted a strengths-based approach to investigating associations between SDT's need satisfaction and job outcomes in Australian Indigenous and non-Indigenous professionals and non-professionals. Participants included 1, 146 Indigenous (48.8%) and non-Indigenous Australians (39.1% men), aged 18 to 81 years ( M age  = 43.54). Structural equation modeling (SEM) revealed that autonomy and competence need satisfaction were associated with multiple positive work outcomes and less job ambiguity, whereas satisfaction of the need for relatedness was associated with increased job satisfaction and greater resilience in the workplace. Moderation by Indigenous status and occupation type revealed few differences in the direction and strength of the associations between need satisfaction and job outcomes. However, non-professionals reported significantly lower satisfaction of all three needs, and Indigenous participants reported significantly lower levels of autonomy need satisfaction. As need satisfaction was shown to be equally beneficial for all workers regardless of culture or occupation type, these findings highlight the need for employers to invest more in cultivating the need satisfaction of their Indigenous and non-professional staff. Overall, the results extend upon previous research by demonstrating that SDT is generalizable to an Australian Indigenous population and that workplace need satisfaction is important for Indigenous and non-professional employee outcomes.